The Effects of Leadership Style, Resource Allocation, and School Culture on Teacher Job Satisfaction and Retention Rates in Indonesian High Schools - Tarigan, Budi Akhmad; Nurmiati, Ai Siti (IJBLE Scientific Publications Community Inc., 2024)
In this quantitative study, teacher job satisfaction and retention rates in Indonesian high schools are examined as a function of school culture, resource allocation, and leadership style. In the study, 276 instructors from various high schools in Indonesia were included as a sample. A structured questionnaire was used to gather the data, and structural equation modeling with partial least squares (SEM-PLS) was used for analysis. The findings show a strong positive correlation between teacher job satisfaction, school culture, resource allocation, transformational leadership, and retention rates. Three factors stand out as critical indicators of teacher job satisfaction and retention: transformational leadership, appropriate resource allocation, and a strong school culture. The aforementioned results highlight the significance of promoting supportive leadership behaviors, guaranteeing adequate resource allocation, and establishing favorable school environments in order to improve teacher retention and well-being in Indonesian secondary education.